2023
DOI: 10.1242/dmm.049811
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-based knockout and base editing confirm the role of MYRF in heart development and congenital heart disease

Abstract: High-throughput DNA sequencing studies increasingly associate DNA variants with congenital heart disease (CHD). However, functional modeling is a crucial prerequisite for translating genomic data into clinical care. We used CRISPR-Cas9-mediated targeting of 12 candidate genes in the vertebrate model medaka (Oryzias latipes), five of which displayed a novel cardiovascular phenotype spectrum in F0 (crispants): mapre2, smg7, cdc42bpab, ankrd11 and myrf, encoding a transcription factor recently linked to cardiac-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 88 publications
0
0
0
Order By: Relevance
“…According to the published data, the individuals diagnosed with HLHS exhibit de novo mutations in both the N-terminal and C-terminal segments of the MYRF protein, indicating a complex underlying mechanism. The association between Myrf and HLHS has been further investigated using CRISPR-Cas9 technology in the vertebrate medaka model, and the Myrf mutant line exhibited a significantly prominent hypoplastic ventricle, which closely recapitulates the phenotypes observed in pediatric patients [129]. Overall, the signaling mechanism by which Myrf contributes to the pathogenesis of HLHS remains unclear, and there is limited knowledge in this area.…”
Section: Myrfmentioning
confidence: 95%
See 1 more Smart Citation
“…According to the published data, the individuals diagnosed with HLHS exhibit de novo mutations in both the N-terminal and C-terminal segments of the MYRF protein, indicating a complex underlying mechanism. The association between Myrf and HLHS has been further investigated using CRISPR-Cas9 technology in the vertebrate medaka model, and the Myrf mutant line exhibited a significantly prominent hypoplastic ventricle, which closely recapitulates the phenotypes observed in pediatric patients [129]. Overall, the signaling mechanism by which Myrf contributes to the pathogenesis of HLHS remains unclear, and there is limited knowledge in this area.…”
Section: Myrfmentioning
confidence: 95%
“…Multiple studies reported that point mutations of myelin regulatory factor (MYRF) are associated with the occurrence of HLHS [129][130][131], suggesting the possibility that monogenic mutations can cause HLHS. Myrf is a vital membrane-bound transcription factor involved in the development of the urogenital, neural, visual, and cardiac systems [132][133][134][135][136].…”
Section: Myrfmentioning
confidence: 99%